Macrocyclic polyamine‐functionalized silica as a solid‐phase extraction material coupled with ionic liquid dispersive liquid–liquid extraction for the enrichment of polycyclic aromatic hydrocarbons. Issue 8 (10th March 2014) - Liu, Longhui; He, Lijun; Jiang, Xiuming; Zhao, Wenjie; Xiang, Guoqiang; Anderson, Jared L.
<x xml:space="preserve">Abstract</x> In this study, silica modified with a 30‐membered macrocyclic polyamine was synthesized and first used as an adsorbent material in SPE. The SPE was further combined with ionic liquid (IL) dispersive liquid–liquid microextraction (DLLME). Five polycyclic aromatic hydrocarbons were employed as model analytes to evaluate the extraction procedure and were determined by HPLC combined with UV/Vis detection. Acetone was used as the elution solvent in SPE as well as the dispersive solvent in DLLME. The enrichment of analytes was achieved using the 1, 3‐dibutylimidazolium bis[(trifluoromethyl)sulfonyl]imide IL/acetone/water system. Experimental conditions for the overall macrocycle‐SPE–IL‐DLLME method, such as the amount of adsorbent, sample solution volume, sample solution pH, type of elution solvent as well as addition of salt, were studied and optimized. The developed method could be successfully applied to the analysis of four real water samples. The macrocyclic polyamine offered higher extraction efficiency for analytes compared with commercially available C18 cartridge, and the developed method provided higher enrichment factors (2768–5409) for model analytes compared with the single DLLME. Good linearity with the correlation coefficients ranging from 0.9983 to 0.9999 and LODs as low as 0.002 μg/L were obtained in the proposed method.